PEMODELAN PRODUK DOMESTIK REGIONAL BRUTO (PDRB) PROVINSI JAWA TENGAH DENGAN PENDEKATAN SPASIAL AUTOREGRESSIVE MODEL PANEL DATA - Ulfatun Khasanah; Abdul Karim; Indah Manfaati Nur (Universitas Muhammadiyah Semarang, 2017)
Modeling spatial is modeling that deals with approach point and area .While regression analysis data panel is regression analysis based on data panel toobserve the relation between one variable bound ( dependent variables ) withone or more variables free ( independent variables). Approach used is themodel spatial autoregressive (SAR). Model spatial autoregresive is a modelcombined model regression simple with lag spatial on the variables ofdependent using data cross section . The data used was data gdp and factorswhich influence it namely the local revenue, population, and investment 20112015year Based on Hausman test for the above model SAR is hisq = 0.50389, df = 3, p-value = 0.918. This means that p-value> 0.05 thus, the selected model is SARrandom effects.Keywords :PDRB, Spatial Panel, Spatial Autoregressive (SAR)